OC33 Altered toll like receptor 2 (TLR2) signalling in children with down syndrome. (June 2019) - Huggard, Dean; Kaoy, Wen J; McGrane, Fiona; Roche, Edna; Balfe, Joanne; Lagan, Niamh; Ryan, Emer; Ronan Leahy, T; Franklin, Orla; Doherty, Derek; Molloy, Eleanor
Abstract : Background: Toll like receptors (TLRs) are key in initiating innate immune responses. TLR2 is crucial in recognising lipopeptides from gram positive bacteria and is implicated in chronic inflammation. Children with Down syndrome (DS) are prone to infections from these pathogens and have an increased risk of autoimmunity. Sparstolonin B (SsnB) is a TLR antagonist shown to reduce cytokine production and improve outcomes in sepsis. We hypothesized that TLR2 signalling may be anomalous in children with DS and contribute to their clinical phenotype. Aims: We aimed to evaluate TLR2 pathways in 3 ways; by determining the expression of TLR2 on the surface of neutrophils, monocytes, and their subsets; examine gene expression of key regulatory proteins involved in TLR signal propagation, MyD88, IRAK4, and TRIF; and lastly to determine cytokine production at baseline and following immunomodulation with pro-inflammatory stimuli (LPS, Pam3Csk4) and the anti-inflammatory agent SsnB. Methods: Whole blood was collected from children with DS and age matched controls. Samples were treated with lipopolysaccharide (LPS) 10ng/ml, Pam3Csk4 (5ng/ml), SsnB (10μM) or in combination. TLR2 and CD11b expression on neutrophils and monocytes was evaluated by flow cytometry. RNA was isolated from Trizol®, cDNA was synthesized and then evaluated by quantitative PCR for expression of MyD88, IRAK4, and TRIF. A panel of pro and anti-inflammatory cytokines were evaluated using the MSD®MULTI-SPOT assay system from Mesoscale (MSD Diagnostics, USA). Statistical analysis employed unpaired t-tests, ANOVA, analysed using GraphPad Prism and FloJo software. Results: Children with DS (n=20) and controls (n=15) were recruited. TLR2 expression was significantly raised on neutrophils (p=0.02), total monocytes (p=0.05), intermediate monocytes (p=0.02) in children with DS compared to controls. At baseline the expression of MyD88 was significantly lower (p=0.001), and TRIF significantly raised in children with DS (p≤0.0001). The TLR antagonist SsnB was effective at reducing TLR2 and CD11b expression and abrogating cytokine production in both cohorts. Conclusion: TLR2 pathway is dysregulated in DS. There is greater expression of TLR2 on the surface of neutrophils and monocytes. Downstream signalling is altered with reduced MyD88 and increased expression of TRIF, which may represent compensatory upregulation of MyD88 independent pathways. This altered innate immunity may contribute to chronic inflammation in DS. SsnB attenuates pro-inflammatory mediators and could be of therapeutic benefit.